2019
DOI: 10.31524/bkkmedj.2019.02.020
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Spirituality in People Living with HIV/AIDS: A Qualitative Meta-synthesis

Abstract: The Roles of Spirituality in People Living with HIV/AIDS: A Qualitative Meta-synthesis T he spread of HIV/AIDS continues to be a major problem for public health around the world. People living with HIV/AIDS (PLWHA) steadily climbed from 35.6 to 36.9 million between 2015 and 2017, with 940,000 people dying from HIV/AIDS during the aforementioned period. 1 Similarly, the number of PLWHA in Thailand increased from 445,000 to 450,000 with approximately 15,000 people dying from HIV/ AIDS during the abovementioned p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
0
10
0
2
Order By: Relevance
“…Also, it can promote empathic relationships towards each other such as comforting family members, showing them attention and care, openness to the family member's attitudes and feelings, and honoring them. 4,14,24 The same is true in the study by Chaiyasit et al, 24 that found that people living with HIV/AIDS perceived the role of spirituality as enhancing the feeling of peace and happiness, inner strength, self-acceptance and understanding of illness, promoting self-care, increasing a sense of compassion, maintaining hope and giving meaning to their lives. This reflects a spiritual anchor to help the family maintain and improve their family functioning to transcend the difficult time of living with children with thalassemia.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Also, it can promote empathic relationships towards each other such as comforting family members, showing them attention and care, openness to the family member's attitudes and feelings, and honoring them. 4,14,24 The same is true in the study by Chaiyasit et al, 24 that found that people living with HIV/AIDS perceived the role of spirituality as enhancing the feeling of peace and happiness, inner strength, self-acceptance and understanding of illness, promoting self-care, increasing a sense of compassion, maintaining hope and giving meaning to their lives. This reflects a spiritual anchor to help the family maintain and improve their family functioning to transcend the difficult time of living with children with thalassemia.…”
Section: Discussionmentioning
confidence: 63%
“…This perception influences the feeling of trust in a higher power and this feels more comfortable since the family believes that everything that happens and will happen in the future has already been determined by supernatural power or belief in religion they respect. 24 Illness belief: Illness belief has been instituted over a long time through the interaction or communication within a family by the family elders' teaching. 25 This means it has been deeply rooted and often constitutes the basis for an individual's identity.…”
Section: Discussionmentioning
confidence: 99%
“…Gambaran responden memungkinkan kurangnya pengetahuan tentang penyakit HIV religius dan spiritual karena kurang terpapar informasi keagamaan, serta penyerapan informasi belum optimal (Anetor, 2019;Jayani & Ruffaida, 2020). Religiusitas dan spiritualitas dapat meningkatkan kedamaian dan kebahagiaan, menumbuhkan kekuatan batin, menambah pemahaman terhadap penyakit dan penerimaan diri, meningkatkan motivasi perawatan diri, menemukan arti dan tujuan hidup, memelihara asa dan menciptakan hubungan dan rasa keterkaitan terhadap sesama dan yang lebih penting hubungan dan keterkaitan dengan Maha Pencipta (Chaiyasit et al, 2019).…”
Section: Pembahasanunclassified
“…Religius dan spiritual karena kurang terpapar informasi keagamaan, serta penyerapan informasi belum optimal (Jayani & Ruffaida, 2020). Religiusitas dan spiritualitas dapat meningkatkan kedamaian dan kebahagiaan, menumbuhkan kekuatan batin, menambah pemahaman terhadap penyakit dan penerimaan diri, meningkatkan motivasi perawatan diri, menemukan arti dan tujuan hidup, memelihara asa dan menciptakan hubungan dan rasa keterkaitan terhadap sesama, dan yang lebih penting hubungan dan keterkaitan dengan Maha Pencipta (Chaiyasit, Thong-on, Piboonrungroj, & Kotta, 2019).…”
Section: Pembahasanunclassified